The shop on royal street eaudiobook - White, Karen (Royal Street, 2022)
Nola Trenholm is hopeful for a fresh start in the Big Easy but must deal with ghosts from her past—as well as new ones—in this first book in a spin-off series of Karen White's New York Times bestselling Tradd Street novels.   After a difficult detour on her road to adulthood, Nola Trenholm is looking to begin anew in New Orleans, and what better way to start her future than with her first house? But the historic fixer-upper she buys comes with even more work than she anticipated when the house’s previous occupants don’t seem to be ready to depart.   Although she can’t communicate with ghosts like her stepmother can, luckily Nola knows someone in New Orleans who is able to—even if he’s the last person on earth she wants anything to do with ever again. Beau Ryan comes with his own dark past—a past that involves the disappearance of his sister and parents during Hurricane Katrina—and he’s connected to the unsolved murder of a woman who once lived in the old Creole cottage Nola is determined to make her own...whether the resident restless spirits agree or not.